Comparative analysis of alternative credit risk models: An application on German middle market loan portfolios - Markus Kern; Bernd Rudolph (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
In recent years new methods and models have been developed to quantify credit risk on a portfolio basis. CreditMetrics (tm), CreditRisk+, CreditPortfolio (tm) are among the best known and many others are similar to them. At first glance they are quite different in their approaches and methodologies. A comparison of these models especially with regard to their applicability on typical middle market loan portfolios is in the focus of this study. The analysis shows that differences in the results of an application of the models on a certain loan portfolio is mainly due to different approaches in approximating default correlations. That is especially true for typically non-rated medium-sized counterparties. On the other hand distributional assumptions or different solution techniques in the models are more or less compatible. @Seit einigen Jahren finden sich in Wissenschaft und Bankpraxis neue Methoden und Modelle, um Risiken von Kreditportfolios zu messen. Zu den bekanntesten Vertretern gehören CreditMetrics(tm) , CreditRisk+ und CreditPortfolioView(tm) , welche sich auf den ersten Blick stark im Ansatz und in der Methodik unterscheiden. Im Mittelpunkt der vorliegenden Studie steht ein Vergleich dieser Modelle und zwar insbesondere hinsichtlich ihrer Anwendbarkeit auf ein typisches Portfolio aus mittelständischen Bankkrediten. Die Analyse zeigt, dass Unterschiede in den Ergebnissen zweier Modelle für ein und dasselbe Portfolio vor allem auf unterschiedliche Verfahren in der Approximation von Ausfallkorrelationen zurückzuführen sind. Dies gilt insbesondere für Kredite an nicht-geratete mittelständische Unternehmen.
urn:nbn:de:hebis:30-9801
Keywords: C15; G21; G33; 330; credit risk management; portfolio modelling; medium-sized debtors